Subversive song: Imagining Colossians 1:15–20 as a social protest hymn in the context of Roman empire. (November 2019) - Medley, Mark S.
A connection exists between the Christological hymn of praise and protest in Col 1:15–20 and popular protest music. The connection is the lyrical ability to transform political and socio-cultural realities, as well as to empower and mobilize protest and resistance against imperial power and coercive structures of domination. A special focus is on Billie Holiday's song, "Strange Fruit, " a contemporary model of a protest song in comparison to Col 1:15–20. In the comparison, the Colossians hymn draws upon the political ideology and imagery of the Roman Empire in the form of a counter-discourse, as was Jewish resistance poetry, in ways analogous to how Holiday's "Strange Fruit" evokes the imagery of white racial terror for the sake of raising political consciousness.